Poisson's ratio and volume change accompanying deformation of randomly oriented electrospun nanofibrous membranes - Wong, Dannee; Andriyana, Andri; Ang, Bee Chin; Lee, Jacky Jia Li; Verron, Erwan; Elma, Muthia (Taylor & Francis, 2019)
The present work focuses on the determination of volume change accompanying deformation and Poisson's ratio for electrospun nanofibrous membranes. For this purpose, polyurethane (PU) is considered for the fabrication of electrospun nanofibrous membranes. Three different sample thicknesses are fabricated. Following this, surface morphology analysis and fibre orientation analysis are conducted to investigate the variation of properties between electrospun PU membranes of different thicknesses. Subsequently, PU specimens are subjected to uniaxial extension test where the changes in sample width and thickness are recorded as a function of applied strain. Volume changes are computed while further analysis on the relationship between transverse strains and axial strain provided the values of Poisson's ratio. For all three electrospun PU samples investigated, significant volume changes are observed while the in-plane Poisson's ratio is found to be around 0.55. However, the out-of-plane Poisson's ratio of electrospun PU membranes are not classical and remains undetermined. © 2019, © 2019 Institute of Materials, Minerals and Mining Published by Taylor & Francis on behalf of the Institute.